Diseño de una estrategia de responsabilidad social administrada por la Fundación Quito Tenis y Golf Club para comunidades aledañas. - López Andrade, Geovvanna Natally (2014)
This study aims to design a social responsibility strategy administered by the Quito Tennis y Golf Club foundation to benefit their surrounding communities. The objective is to contribute to economic, educational and health development. We made a macro and micro analysis of the foundation to determine its strengths and weaknesses in order to set objectives and strategies that will allow an integral improvement. We defined many facts such as: mission, vision, values and principles, objectives and strategies to lead to the implementation of the balanced scorecard, which describes the strategy under its four perspectives.